Peningkatan Motivasi dan Hasil Belajar Geografi melalui Model Cooperative Learning Tipe Group Investigation - Suyatinah Suyatinah (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The goal of this practical research is to find out the step of applying the Cooperative Learning model, type Group Investigation. As well as the effect of the model in increasing motivation and learning result on geography subject of XII IPS 2 class of SMA Negeri 1 Banguntapan in the academic year of 2019/2020. The type of practical used is Classroom reseach. The study was conducted from July until October 2019, motivation and learning result as the research objective. The research stages include planning, implementation, observation, and reflection, which were implemented in 2 cycles. Each of the cycles covering 2 learning activities and 1 exam. Data were collected through documentation, questionnaires, observations, and written tests. The obtained data were analyzed quantitatively in the form of percentages, which were then described and conclusions drawn. The implementation of learning that uses the Cooperative Learning model of the Group Investigation type can be well received by students, fosters a positive attitude to collaborate in the learning process, there is a peer tutoring process, that has an impact on students learning motivation from 88, 60% is quite adequate in the first cycle, becoming 93.75% is classified as good in the second cycle. The application of this learning model can also improve learning outcomes for students of class XII IPS 2 of SMA Negeri 1 Banguntapan for the 2019/2020 academic year, which can be seen in learning completeness of 80% in cycle I and 90.32% in cycle II. Teachers should constantly innovate by using varied learning models so that students are always motivated to learn, and the learning outcomes will increase.